Mitochondrial sensitive probe with aggregation‐induced emission characteristics for early brain diagnosis of Parkinson's disease - Huang, Liwen; Zhou, Yutong; Jiao, Di; Ren, Jing; Qi, Yilin; Wang, Heping; Shi, Yang; Ding, Dan; Xue, Xue (Aggregate (Hoboken), 2024)
The early diagnosis of Parkinson's disease (PD) provides opportunities for early intervention to slow the progression of neurological degeneration in patients, particularly as the aging population increases in our society. Among a series of pathological features of PD, mitochondria abnormalities have been identified as central event that occurs at the early stage of PD. However, the method for detecting mitochondrial abnormalities‐associated early PD has not been fully developed. We herein report a specifically mitochondrial targeting probe (named TPA‐BT‐SCP) that is able to characterize mitochondria abnormalities for early diagnosis of PD and monitor PD neurodegenerative progress. The probe is an aggregation‐induced emission (AIE) probe with a strong positive charge, a 3D distorted molecular structure, and a separated HOMO‐LUMO distribution, designed with unique molecular design guidelines. Our research demonstrated that TPA‐BT‐SCP could emit stable and strong fluorescence, and rapidly accumulate in mitochondria due to the negative charge. After intranasal administration of 1‐methy‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP)‐induced PD mice, TPA‐BT‐SCP successfully bypassed the blood−brain barrier to light up the brain, allowing the grading of PD severity based on its high sensitivity. Taken together, this work develops a novel AIE probe that exhibits dramatically high sensitivity to mitochondrial changes and enables noninvasive diagnosis of early PD in the brain. Mitochondrial abnormalities have been identified as central event in the early stage of PD. Here we design a mitochondrial‐sensitive AIE probe TPA‐BT‐SCP with strong positive charge. As TPA‐BT‐SCP probe emits stable and strong fluorescence and rapidly accumulates in mitochondria, we thus utilize TPA‐BT‐SCP to grade the severity of PD by intranasal administration in MPTP‐induced PD mice.